GAMBARAN HISTOLOGI LIDAH DAN ESOFAGUS Iguana iguana SEBAGAI REPTIL HERBIVORA - , RIKA NOORSUKMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Iguana iguana is the first of domesticated reptiles, but the existence of Iguana iguana lovers community increase by times. One of the common problems in the maintenance of reptiles is feeding errors. Knowledge on the structure of digestive system, especially the tongue and esophagus of Iguana iguana is not well documented, so it is necessary to study its normal microscopic structure. The study use three iguanas from East Java. Before dissection and collection of the tongue and esophagus, the animals were anasthesized by chloroform. The digestive organs were prepared for gross anatomy observation and then samples were fixed in Bouin's solution. After fixation for 24 hours in Bouin's solution, and the samples then transferred to alcohol (70%). Organ samples were dehidrated, embedded in parraffin wax, and sectioned in 5Î¼m thick. Sections were stained with HE and AB-PAS methods. The data of histological structure and mucopolysaccharide distribution of the tongue and esophagus were analyzed descriptively. The tongue of Iguana iguana has a high filiform papillae at the apex to the middle, then getting shortening toward the hindtongue become conical papillae. Filiform papilae covered by stratified squamous epithelium in the apex, and columnar simplex on lateral papillae. Taste bud found in very small amounts. Epithelial cells and mucous glands in the lamina propria mucosa shows positive reaction to the AB-PAS. The muscle layer of the tongue is composed of striated muscles and there is hyalin cartilage. The esophageal mucosa Iguana iguana was folded and lining with pseudostratified ciliated columnar epithelium with goblet cells. Epithelial cells shows positive reaction to the AB-PAS. There are no glands. In the cranial portion of esophagus the muscle layer consists of only smooth muscles, while the caudal portion is composed of smooth muscles in the inner circular layer and striated muscles in the longitudinal muscle layer. Over all, the microscopic structure of the tongue and esophagus Iguana iguana same with the other reptile, except in keratinization of epithelium, filiform and conical papillae, few taste bud, and hyalin cartilage in the muscle layer of tongue. In the cranial potions of esophagus the muscle layer consists of only smooth muscles, while the caudal potion is composed of smooth muscle in the inner circular layer and striated muscle in the longitudinal muscle layer. The serosa layer composed of collagen connective tissue.